2020
DOI: 10.1007/s00415-020-10002-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact of COVID-19 in Parkinson’s disease: evidence from a multi-center survey in Tuscany region

Abstract: Background If Parkinson's Disease (PD) may represent a risk factor for Coronavirus disease 2019 (COVID-19) is debated and there are few data on the direct and indirect effects of this pandemic in PD patients. Objective In the current study we evaluated the prevalence, mortality and case-fatality of COVID-19 in a PD cohort, also exploring possible risk factors. We also aimed to investigate the effect of lockdown on motor/non-motor symptoms in PD patients as well as their acceptability/accessibility to telemedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
119
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(135 citation statements)
references
References 28 publications
5
119
2
3
Order By: Relevance
“…Although prior studies have reported higher SARS-CoV-2-related mortality in patients with PD or dementia compared to patients without preexisting neurodegenerative diseases, 6,7 encouragingly, our comparably relatively large, well-controlled, standardized data set with prospective patient enrollment does not support the notion of an increased risk for a fatal course of SARS-CoV-2 in PD or dementia patients, when treated in tertiary referral centers. Further research is required to shed light on the impact of gender on the outcome of SARS-CoV-2 infections in dementia patients.…”
contrasting
confidence: 72%
“…Although prior studies have reported higher SARS-CoV-2-related mortality in patients with PD or dementia compared to patients without preexisting neurodegenerative diseases, 6,7 encouragingly, our comparably relatively large, well-controlled, standardized data set with prospective patient enrollment does not support the notion of an increased risk for a fatal course of SARS-CoV-2 in PD or dementia patients, when treated in tertiary referral centers. Further research is required to shed light on the impact of gender on the outcome of SARS-CoV-2 infections in dementia patients.…”
contrasting
confidence: 72%
“…A single-centre, case-controlled telephone survey indicated that morbidity and mortality in patients with mild to moderate PD did not differ from those in the general population [ 22 ]. Conversely, a later phone survey showed that the COVID-19 prevalence among PD patients in Italy is higher than the national average [ 23 ]. These studies provide useful insights into the vulnerability of PD patients, but several methodological inconsistencies hamper their interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…11 Conversely, another telephone survey suggested a higher prevalence of COVID-19 compared with that expected for the general population. 15 Trying to overcome the limitations of these studies, we designed a population-based study investigating the risk for hospital admission of COVID-19 and the risk of death in people with PD or PS.…”
mentioning
confidence: 99%